2007
DOI: 10.1152/ajprenal.00505.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 is downregulated in cisplatin-induced apoptosis, and proteasome inhibitors restore Mcl-1 and promote survival in renal tubular epithelial cells

Abstract: Mcl-1 is an antiapoptotic member of the Bcl-2 family that plays an important role in cell survival. We demonstrate that proteasome-dependent regulation of Mcl-1 plays a critical role in renal tubular epithelial cell injury from cisplatin. Protein levels of Mcl-1 rapidly declined in a time-dependent manner following cisplatin treatment of LLC-PK(1) cells. However, mRNA levels of Mcl-1 were not altered following cisplatin treatment. Expression of other antiapoptotic members of the Bcl-2 family such as Bcl-2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 59 publications
5
19
1
Order By: Relevance
“…Given the critical role that Bcl-2 family proteins and p53 protein play in apoptosis regulation (12,66), expression of these apoptosis-related molecules was monitored. In line with a previous report (64) showing that cisplatin induces reduction of Mcl-1 in renal tubular epithelial cells, protein levels of Mcl-1 exhibited mild decreases in HepG2-con cells after exposure to cisplatin; interestingly, levels of Mcl-1 displayed even more dramatic decreases in HepG2-HBx cells than in control cells after cisplatin treatment ( Fig. 2A).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Given the critical role that Bcl-2 family proteins and p53 protein play in apoptosis regulation (12,66), expression of these apoptosis-related molecules was monitored. In line with a previous report (64) showing that cisplatin induces reduction of Mcl-1 in renal tubular epithelial cells, protein levels of Mcl-1 exhibited mild decreases in HepG2-con cells after exposure to cisplatin; interestingly, levels of Mcl-1 displayed even more dramatic decreases in HepG2-HBx cells than in control cells after cisplatin treatment ( Fig. 2A).…”
Section: Resultssupporting
confidence: 92%
“…In view of the key role of the Bcl-2 protein family in the regulation of cell survival and death, we examined the expression of several Bcl-2 family members. Interestingly, among the apoptosis-related proteins detected, only protein levels of Mcl-1 were reduced dramatically in HBx-expressing hepatocytes following treatment with cisplatin, which was consistent with the finding of a previous study that Mcl-1 was downregulated during cisplatin-induced apoptosis in renal tubular epithelial cells (64). Furthermore, similar results were also observed in an HBx-inducible expression system, HBVreplicating HepG2.2.15 cells, and SMMC-7721 cells transfected with the wild-type but not HBx-mutated HBV genome.…”
Section: Discussionsupporting
confidence: 91%
“…Sorafenib, a Food and Drug Administration-approved agent in the treatment of renal cell carcinoma, has been shown to decrease Mcl-1 in an AML model (32). Cisplatin, a first-line agent in the treatment of SCLC, decreases Mcl-1 levels in human renal tubular epithelial cells (33). The primary xenografts may serve as representative models that test combinatorial therapies with agents that down-regulate multiple members of the Bcl-2 family.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine is the first-line chemotherapeutic agent for advanced adenocarcinoma of pancreatic cancer; however, chemoresistance to gemcitabine remains a major cause of failure for the clinical treatment of this disease. Studies have indicated that resistance to gemcitabine is dependent on mitochondria-mediated apoptosis, but various mediators of gemcitabine-mediated apoptosis have been described (40)(41)(42)(43). The precise mechanism is not fully understood.…”
Section: Discussionmentioning
confidence: 99%